Organizational coordination and patient satisfaction: a structural analysis of healthcare quality in Durgapur, India - Sahoo, Pabitra; Khatun, Yasmin (International Journal Of Community Medicine And Public Health, 2025)
Background: Healthcare organizations are complex systems that require effective coordination among departments and teams to deliver optimal patient care. Organizational coordination involves the intentional integration of activities and resources to achieve common goals. This study will explore the relationship between organizational coordination and patient satisfaction in a Durgapur, India healthcare facility, offering insights to enhance quality and improve patient experiences. Methods: A cross-sectional survey was conducted rigorously at a tertiary hospital in Durgapur to investigate patient satisfaction. A robust sample of 167 patients was used for the data collection process, which was meticulously executed through a comprehensive questionnaire administered over a period of three months. Results: The demographic analysis highlighted that 55.69% of respondents were male and 44.31% were female. Harman’s single-factor test showed a total variance of 23.06%, indicating no significant common method bias. The measurement model assessment confirmed strong internal consistency (Cronbach’s α>0.7) and composite reliability (CR>0.7), along with satisfactory convergent and discriminant validity (AVE>0.5). The structural model demonstrated a good fit (χ²/df=2.378, GFI=0.944, CFI=0.949, AGFI=0.873, RMSEA=0.09). Most importantly, the relationship between organizational coordination and patient satisfaction was statistically significant (β=0.209, C.R.=6.815, p<0.01). Conclusions: This study demonstrates that strong organizational coordination significantly boosts patient satisfaction in Durgapur’s healthcare system. By integrating vital operational factors, our proposed model delivers a comprehensive framework designed to elevate care quality, enhance communication, and enrich the overall patient experience.